2005
DOI: 10.1021/ma048192w
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior and Photooptical Properties of Liquid Crystalline Functionalized Copolymers with Low-Molecular-Mass Dopants Stabilized by Hydrogen Bonds

Abstract: The approach of deriving new photooptically active polymeric substances by hydrogen bonding between functionalized liquid crystalline (LC) copolymers and low-molecular-mass dopants, containing photochromic azobenzene fragments, is described. The formation of intermolecular hydrogen bonds between carboxylic groups of functionalized LC copolymers and the pyridine fragment of the dopant leads to stable, nonseparating mixtures in a broad interval of contents (up to 30 mol % dopant molecules). The phase behavior an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 20 publications
(11 reference statements)
2
36
0
5
Order By: Relevance
“…As early examples of photoinduced anisotropy in supramolecular complexes, Medvedev et al 98 and Cui and Zhao 99 showed that the liquid crystallinity and photo-orientation capability of covalently functionalized side-chain polymers can be modified by hydrogen bonding small molecules to the side-chain extremities. In both cases, the inscribed anisotropy was temporally relatively stable (up to remnant anisotropies of 80% or more), like in covalent azobenzene-containing polymers reported earlier.…”
Section: Photoinduced Anisotropymentioning
confidence: 99%
“…As early examples of photoinduced anisotropy in supramolecular complexes, Medvedev et al 98 and Cui and Zhao 99 showed that the liquid crystallinity and photo-orientation capability of covalently functionalized side-chain polymers can be modified by hydrogen bonding small molecules to the side-chain extremities. In both cases, the inscribed anisotropy was temporally relatively stable (up to remnant anisotropies of 80% or more), like in covalent azobenzene-containing polymers reported earlier.…”
Section: Photoinduced Anisotropymentioning
confidence: 99%
“…The drawback of these systems is the fact that for each combination of a polymer and an active molecule an organic synthesis is required which makes the sample preparation slower and more expensive. Alternative and thus the another way of preparation of azobenzene-containing polymers is the utilization of different nonconvalent intermolecular interactions hydrogen bond [5,27,[39][40][41][42][43][44][45][46][47]. Such approach offers a new convenient way to link the active molecules to the polymer chains thereby problems with often complicated synthetic routes for the preparation of the polymers with covalently bonded chromophores are eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…Passive optical devices such as birefringent films and polarization holographic gratings have been fabricated using these molecular reoriented films [3][4][5]. Furthermore, cooperative photoinduced molecular orientation allows to introduce the functionality of the reoriented films by tuning the comonomers with non-photoreactive mesogenic side groups [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%